PARTNERSHIP MANAGEMENT AND POTATO COMPETITIVENESS IN BENER MERIAH DISTRICT, ACEH PROVINCE - Nurmala, Nurmala; Sullaida, Sullaida; Zahara, Hafni; Jamilah, Jamilah; Saputra, Jumadil (Universitas Brawijaya, Indonesia, 2023)
The research aims to identify supply chain partnerships and analyze potato competitiveness. The research location is in Bener Meriah Regency, Aceh Province. Supply chain partnership management is studied using qualitative and quantitative descriptive approaches. Potato competitiveness was analyzed using the Policy Analysis Matrix (PAM) approach. The research results show that potato farming is quite profitable for farmers and has competitiveness as a superior product. Potato farming partnerships are carried out by farmers at the level of seed procurement and farming costs with a profit-sharing system or general trading pattern through farming capital loans with the condition that farmers must sell potatoes to traders at below-market prices. Potato farming in Bener Meriah Regency has comparative advantages and competitive advantages. It is worthy of development based on the acquisition of PCR and DRCR, both of which have a value of more than one. Potato farming has good prospects for intensive development to increase the competitiveness of potatoes through synergistic partnership programs with downstream business players, considering the high market demand for potatoes and processed potato products.